Literature review on cattle blood polymorphisms and preliminary results of analysis in East African Zebu in Ethiopia - Cecchini, G.; Nijs, M. de (1986)
A literature review on five blood polymorphisms, namely haemoglobin, carbonic anhydrase, transferrin, amylase and albumine is presented with a description of the possible correlation to animal performances. The preliminary results of a trial experiment done in Ethiopia on 26 Small East African Zebu type of cow (24 females and 2 males) are reported and compared with results of other authors.